Nivel de vacilación frente a la vacuna contra COVID-19 en una zona urbano marginal de Lima: Level of hesitancy towards the COVID-19 vaccine in a marginal urban area of Lima - Guerra-Pizango, Lucia Angelica (2022)
Objective: To determine the frequency and the factors associated with the refusal of vaccination against COVID-19 in the marginal urban area of Lima. Materials and methods: Quantitative, observational and descriptive cross-sectional study carried out in the year 2021. The population was made up of residents of the "Nueva Juventud" Human Settlement located in the district of Carabayllo, in the North of Lima. The study variable was the refusal of vaccination against COVID-19. Results: 405 people of both sexes participated with a median age of 30 years (Q1: 23, Q3: 42, Interquartile range: 19). Of the sample, 47.9% (n=194) were between 18 and 29 years old, 62% (n=251) corresponding to the female sex, most of the participants had a higher education degree and were users of the Comprehensive Health Insurance (SIS). 64% (n=259) reported a history of COVID-19. Regarding the level of hesitation, in 21.5% (n=87) it was low, 48.6% (n=197) moderate and 29.9% (n=121) presented a high level of hesitation. The high level of hesitation occurred in a greater proportion in older residents (p<0.001) and people with a lower level of education (p=0.001). The lowest percentage of high hesitation was presented in users of the SIS (p=0.005). Conclusions: There is a predominance of moderate and high level of hesitation against the COVID-19 vaccine. High hesitation was greater in older people and in those with a lower level of education. It is recommended to improve communication strategies regarding the benefits of the COVID-19 vaccine.  Keywords: Vaccination Refusal; COVID-19; COVID-19 Vaccines; Peru (Source: MeSH, NLM).